Analysis of Google Sites Media Needs to Improve Historical Thinking Skills in Local History Learning at SMAN 16 Palembang - Pravia Indwi Saputri; Muhamad Nur Rokhman (Universitas Hamzanwadi, 2026)
This study aims to analyze the need for Google Sites media development to improve students' historical thinking skills in local history learning at SMAN 16 Palembang. The method used is descriptive research with data collection through questionnaires, observations, interviews, tests, and documentation. The results show that current history learning is still conventional, with minimal digital media, and students' historical thinking skills, especially in the Big Six Historical Thinking Concepts indicator, are still low. The findings also reveal that web-based digital media, specifically Google Sites, has great potential to become an interactive learning medium that supports the presentation of local history material contextually, increases student engagement, facilitates analysis of historical evidence, and encourages reflection on historical values ​​and perspectives, thereby improving the quality of history learning overall.